2017
DOI: 10.12973/eurasia.2017.00738a
|View full text |Cite
|
Sign up to set email alerts
|

A Study of The Influence of Organizational Learning on Employees’ Innovative Behavior and Work Engagement by A Cross-Level Examination

Abstract: The purpose of this study is to examine the influence of organizational learning on employee's innovative behavior, and further proposed the mediation effect of work engagement between the relationship of organizational learning and employee's innovative behavior. The study targets on executives and their subordinates by paired samples within the Southern Taiwan Science Park and a total of 21 useful firms collected, including 54 managers and 511 employees, and to evaluate research model by using hierarchical l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
32
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 19 publications
5
32
0
4
Order By: Relevance
“…Likewise, knowledge sharing can trigger employee innovation behaviour because the knowledge shared with employees forms trust in the organization (Akhavan et al, 2015). Furthermore, organizational learning can trigger innovation because organizational learning simplifies the process of employee tasks (Lin & Lee, 2017). Therefore, transformational leadership, knowledge sharing, and organizational learning had a positive effect on improving the innovative work behaviour of employees in the company.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, knowledge sharing can trigger employee innovation behaviour because the knowledge shared with employees forms trust in the organization (Akhavan et al, 2015). Furthermore, organizational learning can trigger innovation because organizational learning simplifies the process of employee tasks (Lin & Lee, 2017). Therefore, transformational leadership, knowledge sharing, and organizational learning had a positive effect on improving the innovative work behaviour of employees in the company.…”
Section: Discussionmentioning
confidence: 99%
“…Eldor & Harpaz also explains that the learning climate in an organization is important in encouraging competitiveness which is a reflection of the innovative behavior of organizational members [11]. Studies conducted by Lin & Lee also proved that organizational learning is a factor that significantly influences innovative behavior [12]. Especially in the public environment, research conducted by Miao, Newman, Schwarz, and Cooper also showed the important role of leadership in influencing innovative behavior [13].…”
Section: Introductionmentioning
confidence: 97%
“…Eldor (2011) also states that the innovative behavior of each member of the organization is a reflection of an organization that carries out learning and encourages organizational competitiveness. Another study conducted by Lin and Lee (2017) proves that organizational learning is a factor that significantly influences innovative behavior.…”
mentioning
confidence: 97%